Aplikasi Jasa Titip Belanja Berbasis Mobile di Minahasa Utara - Stenly Ibrahim Adam; Mark Jibril Mononutu; Glainhard Damping (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
Shopping is an activity that humans do to fulfill their basic daily needs. There are many ways to shop today, one of which is shopping online. Shopping online makes it easy for people to shop from home without having to go to the store and not having to worry about wasting time, so shopping online is the best choice because it is more practical and efficient. Therefore, the researcher aims to design a mobile application for Supermarket Shopping Pickup Services in North Minahasa. The design of this application uses the Scrum method with the technology used is the Javascript programming language with React Native and ReactJS frameworks, and Firebase as the database used. The final result of this research is a mobile application for customer and courier users, as well as a web application for admin and store users. Both applications have been tested and run well. The benefit of this research is that it makes it easier for people to fulfill their shopping needs and can provide additional income for people who want to become couriers in this application.